Teacher Assessment of School Readiness on Motoric Aspect of Children Ages 5-6 Years in State Kindergartens in Pekanbaru - Chairilsyah, Daviq (Proceedings of the UR International Conference on Educational Sciences, 2018)
This research is to know teachers assessment of school readiness for children aged 5-6 years in state kindergartens in Pekanbaru (Motoric Aspect). The population in this research is all children aged 5-6 years in all state kindergartens in Pekanbaru amounted to 325 children with total sample of 150 children. The method used is quantitative descriptive method to know the teachers assessment of school readiness in children aged 5-6 years. Data collection technique used observation sheet. Based on the results of data analysis, it was obtained the findings that the percentage of 6 indicators of school readiness in children aged 5-6 years in allstate kindergartens in Pekanbaru such as: Children can run (72.36%) at state kindergartens in Pekanbaru is high,so the motoric readiness of children in kindergarten can be categorized as Developing As Expections, Children can kick the ball (75.27%) is high, so motoric readiness of children in kindergarten can be said Developed As Expectations, Children can balance the body in plank board (72.72%) is also high so motoric readiness of children in kindergarten can be said Developing As Expectations, Children can play fingers (72,90%) pertained high, then the motoric readiness of children in kindergarten can be categorized Developing As Expectations, Children can âmeronceâ (string up) (76.36%) is very high, so then the motoric readiness of children in kindergarten can be said Very Good Developing (BSB), and indicator of Children can color a certain image pattern is very high (76.36%), so motoric readiness of children in kindergarten can be said Developing Very Good. The overall of readiness in motoric aspect at state kindergartens in Pekanbaru iscategorized high (74.33%), so motoric readiness of children in kindergarten can be said Developing As Expectations.